Quantification of FITC-labelled probiotic Lactobacillus salivarius DSPV 001P during gastrointestinal transit in broilers - Blajman, Jesica (2017)
The knowledge related to the fate of probiotics in the complex environment of the intestinal microbiota in broilers is just beginning to be elucidated; however, it is not yet well understood. A good method to investigate the mechanisms by which probiotics mediate their effects is to mark probiotic bacteria and trace them. The aim of this research was to develop a new method to estimate in vivo fluorescein isothiocyanate (FITC)-labelled Lactobacillus salivarius DSPV 001P counts during passage through the gastrointestinal tract (GIT) of broilers. Forty-five, 1 d old Cobb broilers were used in this trial. Programmed necropsies were performed 30 min, 6 h, and 12 h after the administration of the probiotic bacterium, and samples of liver, crop, duodenum, caecum, and bursa of fabricius were collected. To determine the spatial and temporal transit of L. salivarius DSPV 001P in broilers, the number of bacteria as well as its respective fluorescent signal produced by FITC were measured. In order to observe the relationship between the variables, a logistic regression analysis was applied. The amount of fluorescence could be used as an indicator of fluorescent probiotic bacteria in the crop and duodenum 30 min after probiotic bacterium supplementation. In addition, the fluorescent signal could be used to estimate bacterial counts in caecum 6 and 12 h after L. salivarius DSPV 001P administration. To the best of our knowledge, this research is the first in vivo trial to employ the bacterial FITC-labelling technique in order to enumerate probiotic bacteria during gastrointestinal transit in broilers.